Low frequency vibrations in disc brakes at high car speed. Part I: experimental approach. (4th August 2014) - Aviles, R.; Hennequet, G.; Hernandez, A.; Llorente, J.I.
The aim of the present paper is to describe a study carried out into low–frequency vibrations in disc brakes. The vibrations which we will describe occur when braking is initiated at high speed and under medium pressures. Experiments, both vibratory and thermal, were conducted in a car and on a dynamometric bench. The brake pads were submitted to tribological tests. The modes and frequencies of vibration were determined experimentally and by means of a finite–element model, and the two foci were correlated. An analysis was made of the noise produced in the car and of its relation to brake vibration. This vibration, which can be considered a form of judder, proved amenable to such examination. It was possible to determine the causes and to prescribe a means of amelioration in the given case. Part II of this paper deals with the mathematical modelling and with computer simulation.